Index of the Project Gutenberg Works of Frederic Remington - Remington, Frederic, 1861-1909; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2019)
"Index of the Project Gutenberg Works of Frederic Remington" by Frederic Remington is a comprehensive compilation of various writings by the author, encompassing works from the late 19th to early 20th century. This collection includes narratives that explore themes surrounding the American frontier and the interactions between Native Americans and settlers, making it a significant historical account. It serves as an introduction to Remington's contributions to literature, illustrating his fascination with the American West through his vivid storytelling and accompanying illustrations. The book features an index of Frederic Remington's works, including notable pieces like "The Way of an Indian," "Crooked Trails," and "Red Men and White." Each title offers unique narratives that delve into the lives of Indigenous peoples and the challenges they faced during the frontier period, as well as the experiences of settlers and soldiers. Through a mix of illustrated storytelling and engaging prose, Remington captures the essence of the wild, rugged landscape and its inhabitants, while providing commentary on the cultural exchanges and conflicts inherent in that era. This collection stands as a valuable resource for those interested in American history and literature from this transformative period. (This is an automatically generated summary.)
Release date is 2019-06-03
Produced by David Widger
Keywords: Indexes